1981
DOI: 10.1039/f29817701129
|View full text |Cite
|
Sign up to set email alerts
|

Strictly localized molecular orbitals

Abstract: Some possibilities and limitations of the strictly localized model of molecular wave functions are discussed in the light of C N D 0 / 2 calculations. The analysis of non-orthogonal localized molecular orbitals obtained from usual SCF wavefunctions gives some insight into the effects omitted from the strictly localized model.Recently Barone et al.' applied a procedure giving self -consistent, strictly localized molecular orbitals. They separated approximately the C N D 0 / 2 or INDO Fock matrices into 2 x 2 bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…One can use some standard completely transferrable set of values for the h i bond polarities, determined, e.g., by the electron negativities of the atoms between which the bond in question is formed [ l l , 201. It seems, however, it is more appropriate to determine the polarities fully variationally [12][13][14]211. This means that we solve the 2 x 2 HFR problem for each bond incorporating the influence of all other bonds on the given one into the effective core.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One can use some standard completely transferrable set of values for the h i bond polarities, determined, e.g., by the electron negativities of the atoms between which the bond in question is formed [ l l , 201. It seems, however, it is more appropriate to determine the polarities fully variationally [12][13][14]211. This means that we solve the 2 x 2 HFR problem for each bond incorporating the influence of all other bonds on the given one into the effective core.…”
Section: Methodsmentioning
confidence: 99%
“…For example, qualitative reproduction of molecular electrostatic potentials is already possible by using completely transferable SLBOS [ll]. Net atomic charges, bond lengths, bond angles, and multipole moments can be calculated with sufficient accuracy, if inductive effects are also accounted for, but without departing from the strictly localized BOS [12][13][14]. Rotational barriers around single bonds, however, cannot be reproduced correctly if tails of orthogonal localized BOS are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…In this way orbitals strictly localized on few atoms, namely, extremely localized molecular orbitals or ELMOs, are obtained. 31,32 Unfortunately, as already observed by several authors, [33][34][35][36][37][38][39][40][41][42][43][44] an important problem connected with the ELMO description is that the energy associated with the ELMO wavefunction is, not unexpectedly, higher than the corresponding Hartree-Fock one. 21 Moreover, through a series of preliminary studies we have shown the transferability of ELMOs, 20,[22][23][24][25]28 which has stimulated us to develop DENPOL, 26,28 a program that allows for the computation of ab initio quality electron densities for polypeptides through a database of suitable model compounds for all the aminoacids and a database of extremely localized molecular orbitals determined for these model molecules.…”
Section: Introductionmentioning
confidence: 95%
“…For closed-shell classical molecules we define one-center lone pairs, two-center u-, and many-center a-orbitals [19][20][21][22][23] 4: For the subsystem we expand the wavefunction on the basis HYOS (2Ns is the number of electrons in the subsystem):…”
Section: Basis Setmentioning
confidence: 99%